1993
DOI: 10.1063/1.353401
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hydrogenated GaAs/AlGaAs multiple quantum well structures

Abstract: We report on the photoluminescence properties and the hydrogen depth distributions of plasma treated GaAs/AlGaAs multiple quantum well (MQW) structures. Specimens grown by molecular beam epitaxy were exposed to a deuterium plasma under different temperature-time conditions. Photoluminescence measurements were made at 4.2 K, using low and high excitation powers, on the hydrogenated samples and on untreated partners. A decrease in the linewidth of the free exciton and an increase in the peak intensity were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…al. [7]. In our sample, this band does not show any variation in peak position with excitation intensity and could not be involving any prominent D-A pair transition.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…al. [7]. In our sample, this band does not show any variation in peak position with excitation intensity and could not be involving any prominent D-A pair transition.…”
Section: Resultsmentioning
confidence: 68%
“…After hydrogenation, D-V transition becomes dominant due to acceptor passivation. In an earlier work by Swaminathan and co workers [7], a new near band edge peak was observed which was attributed to hydrogenation induced damage. We observe such a peak in InP : Zn samples and explain it as the D-A pair transition which becomes observable following acceptor passivation by hydrogen.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is well known that hydrogen in bulk samples as well as in quantum well (QW) structures saturate the dangling bond, passivates both shallow dopants and deep centers by forming hydrogen impurity complexes [1][2][3][4][5][6][7]. Gal et al [8] observed the neutralization of interface defects caused by misfit dislocations, in partially relaxed In y Ga 1Ky As/GaAs heterostructures by hydrogen plasma.…”
mentioning
confidence: 99%